1996
DOI: 10.1152/jappl.1996.81.3.1331
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of pulmonary oxygen uptake and muscle phosphates during moderate-intensity calf exercise

Abstract: The purpose of this study is to directly compare the dynamic responses of phosphocreatine (PCr) and P(i) to those oxygen uptake (VO2) measured at the lung during transitions to and from moderate-intensity exercise. Changes in PCr and P(i) were measured by 31P-nuclear magnetic resonance spectroscopy, and changes in VO2 were measured breath by breath by mass spectroscopy during transitions to and from moderate-intensity square-wave ankle plantar flexion exercise in 11 subjects (7 men and 4 women; mean age 27 yr)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
123
2
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(143 citation statements)
references
References 0 publications
14
123
2
4
Order By: Relevance
“…kinetics of cardiac output), rather than peripheral factors (blood flow redistribution, mitochondrial density), as is exercise of a smaller muscle mass such as the plantar flexors (Anderson & Saltin, 1985;Shephard, Bouhlel, Vandewalle & Monod, 1988). During exercise of a small muscle mass, it is unlikely that cardiovascular function is challenged, as perfusion is in excess of metabolic demand (Anderson & Saltin, 1985), while, in whole body exercise, demand for 02 may outstrip its supply (Shephard et al 1988 (McCreary et al 1996). Our results (Fig.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…kinetics of cardiac output), rather than peripheral factors (blood flow redistribution, mitochondrial density), as is exercise of a smaller muscle mass such as the plantar flexors (Anderson & Saltin, 1985;Shephard, Bouhlel, Vandewalle & Monod, 1988). During exercise of a small muscle mass, it is unlikely that cardiovascular function is challenged, as perfusion is in excess of metabolic demand (Anderson & Saltin, 1985), while, in whole body exercise, demand for 02 may outstrip its supply (Shephard et al 1988 (McCreary et al 1996). Our results (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…31P MRS 31p spectra collected during both the progressive resistance (ramp) and constant load (square wave) protocols were acquired at 1.5 T with a Siemens Helicon imaging and spectroscopy system and a dual tuned (31P and 'H) surface coil, which measured 5 cm in diameter. Placement of the surface coil over the belly of the lateral gastrocnemius was guided by transverse relaxation (T2) weighted images obtained previously (McCreary et al 1996). These images, along with surface electromyographic measurements indicated that the lateral gastrocnemius was the predominant muscle used during the plantar flexion protocol (McCreary et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O 2 kinetics reflect the kinetics of muscle PCr and thus the rate of muscle O 2 utilisation. Further support for this conclusion can be found in the data presented by McCreary et al [41] Their data showed that PCr and phase 2 V . O 2 kinetics, measured simultaneously during the same moderate exercise task (ankle plantar flexion), occurred at similar rate.…”
Section: O 2 Utilisationmentioning
confidence: 62%
“…The coupling between PCr and O 2 kinetics at the onset of exercise until steady state has been well characterised (Binzoni et al 1992;Barstow et al 1994;McCreary et al 1996;Rossiter et al 1999;Rossiter et al 2001;Rossiter et al 2002;Korzeniewski and Zoladz 2006). The ratio of ATP/ADP and PCr/Cr are linked in the mitochondria to the creatine kinase (CK) reaction (Chance and Williams 1955;Meyer et al 1984;Mahler 1985;Balaban 1990).…”
Section: Cr Supplementation and Endurance (Aerobic) Exercise Performancementioning
confidence: 99%